Do CT values change over time and correlate with hearing in the non-surgical ears of otosclerosis patients?. (2nd December 2022) - Chen, Wei; Fang, Yanqing; Geng, Yue; Lin, Naier; Sha, Yan
Abstract: Background: High-resolution computed tomography (HRCT) is often used to diagnose otosclerosis. Aims/Objectives: To investigate whether CT values change over time and correlate with hearing in the non-surgical ears of otosclerosis patients. Materials and methods: 32 patients with bilateral otosclerosis who had undergone unilateral stapedectomy were enrolled in the study. HRCT examination and pure tone audiometry were performed before and after the surgery. CT values of different regions of interest (ROIs) were measured manually and the data were collected for analysis. Results: The CT value of anterior to the inner auditory meatus (AIAM) decreased by 88.5 HU ( p  < .05), and the changes in CT values in other ROIs showed no statistical difference. Regarding hearing, the value of air bone gap (ABG) increased by 3.6 dB ( p  = .020), and the average hearing deterioration rate of ABG was 3.1 dB/year. The CT value of the mid-point of the stapes footplate (MPSF) showed a certain correlation with the change of ABG ( p  < .05). Conclusions and significance: The CT value of AIAM may change over time. The overall hearing of non-surgical ears in otosclerosis patients shows a deteriorating trend. Moreover, the changes in the CT value of MPSF may be related to the hearing, which needs further research.